Online second-hand shopping motivation – Conceptualization, scale development, and validation. (November 2019) - Padmavathy, Chandrasekaran; Swapana, Murali; Paul, Justin
Abstract: Despite the increasing popularity and growth of online second-hand peer to peer/customer to customer (P2P/C2C) e-commerce, research on online second-hand shopping remains limited. To fill the research gap, this study conceptualizes, develops, and validates a scale to measure online second-hand shopping motivation (OSSM). The findings show that OSSM, as a formative higher-order construct, consists of three second-order factors and nine first-order dimensions: economic motivation (including price orientation, bargaining power, and critical orientation), convenience motivation (usefulness and ease of use), and ideological motivation (need to be unique, nostalgia, trust, and assurances). Further, the study results reveal that OSSM positively predicts attitude and repurchase intention. This study has important implications to the online P2P second-hand firms and the new goods e-retailers.